RANCANG BANGUN APLIKASI MEDIA PEMBELAJARAN TAHSIN AL-QUR’AN BERBASIS ANDROID - Rahma Della; Yasdinul Huda (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
This study aims to design and create a media application for learning the Quran that can be used on Android smartphones by reading and listening to the reading of letters according to their meaning and can immediately be practiced using voice speech. The system development method used is the waterfall method. This application is built on the Android platform and implements voice recognition. Voice recognition algorithm used is devide and conquer to convert sound into discrete form so that synchronization of speech recognition time occurs. The application test results obtained suitability between the algorithm and the design of the application that has been made in accordance with the design objectives. Keywords: tahsin, interactive, android, voice recognation